App-Based Tele Ophthalmology: A Novel Method of Rural Eye Care Delivery Connecting Tertiary Eye Care Center and Vision Centers in India. (18th December 2019) - Das, Anthony Vipin; Mididoddi, Shravani; Kammari, Priyanka; Deepthi Davara, Navya; Loomba, Abhinav; Khanna, Rohit; Taneja, Mukesh
Abstract : Purpose. The study aims to describe a novel method of utilization of the eyeSmart EMR (electronic medical record) app. It describes the demographic distribution, clinical presentation, query requested by the vision technician, and management advised to the patients by using "eyeSmart EMR" app from the vision centers located across a three-tier eye care network in India. Methods. This is a retrospective review of all patients who required a tele-ophthalmology consultation from January 2017 to August 2018. The demographic, clinical details, and the impact of teleophthalmology using eyeSmart app, in the vision centers of a three-tier eye care network, was analyzed in detail. Results. A total of 15, 001 tele-ophthalmology consults were included which is from January 2017 to August 2018. The mean age was 38 ± 19 years and male to female ratio was 1 : 2. Video calls were performed for 6191 (41.27%) consults and the impact was measured. Additional clinical information was received in 65.61% consults through video call. Medical management was advised in 47.07% of patients and 30.30% were referred to higher centers for medical intervention and 0.59% were referred for surgical intervention, 16.23% were prescribed glasses. No intervention required for 0.69% of cases. Hence nil intervention was advised. Conclusion. The combination of using tablet and video calls with the help of eyeSmart EMR app is a novel method in teleophthalmology. It helps in connecting the patients at rural areas and the ophthalmologists in higher centers. The use of technology plays a vital role in the appropriate medical management of the patient.